Sistem Informasi Pengenalan Seni Dan Budaya Jawa Barat Berbasis Java Netbeans - Safirah Rahmah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The purpose of this research is to build a cultural introduction application by utilizing the current development of science and technology so that the introduction of Indonesian culture, especially in West Java, becomes a medium that is able to put education to the public to be able to recognize the many cultures in West Java that are diverse using desktop-based computer media that is more fun. System development using qualitative methods. This application is made with desktop java. With this easy-to-use application, it is hoped that it can provide a solution to help the community in recognizing the culture that exists in West Java.